An Attempt to Maximize the Use of Used Cooking Oil and Fly Ash in the Production of Green Roofing Tile - Teoh, Wei Ping; Chee, Swee Yong; Habib, Noor Zainab; Ng, Choon Aun (International Journal of Sustainable Construction Engineering and Technology, 2022)
This study introduces a novel attempt of utilizing used cooking oil (UCO) and fly ash in the production of green roofing tile, namely UCO-GRT. UCO was utilized as an alternative binder to fully replace the cement and clay, while fly ash was used as a fine aggregate instead of virgin sand. This can maximize the percentage of waste substitution in the manufacturing process, consequently reducing the waste disposal issues encountered in Malaysia. The optimization process was carried out to investigate the optimal manufacturing parameters, by considering the curing duration, the composition of UCO and fly ash, and the composition of catalyst incorporated. The mechanical properties of UCO-GRT produced, including density, dry and wet transverse strength, percentage of water absorption, and permeability have been investigated. Findings reveal that the utilization of catalysed UCO and fly ash solely in the production of roofing tiles is feasible. The optimized UCO-GRT fulfilled the basic requirements of a high-profile roofing tile as per ASTM standards. The embodied carbon and embodied energy of the novel roofing tile were also studied and compared with the cementitious and clay roofing tiles.